Enhancing Sensor Measurements throughWide Baseline Stereo Images - Elias, Rimon (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2008)
In this paper, we suggest an algorithm to enhance the accuracy of sensor measurements representing camera parameters. The process proposed is based solely on a pair of wide baseline (or sparse view) images. We use the so-called JUDOCA operator to extract junctions. This operator produces junctions in terms of locations as well as orientations. Such an information is used to estimate an affine transformation matrix, which is used to guide a variance normalized correlation process that produces a set of possible matches. The fundamental matrix can be easily estimated using the so-called RANSAC scheme. Consequently, the essential matrix can be derived given the available calibration matrix. The essential matrix is then decomposed using Singular Value Decomposition. In addition to a translation vector, this decomposition results in a rotation matrix with accurate rotation angles involved. Mathematical derivation is done to extract angles from the rotation matrix and express them in terms of different rotation systems.